MODEL PENDIDIKAN AGAMA ISLAM PADA SUKU ANAK DALAM DI MES SAD KABUPATEN MURATARA - Eka Purnama Sari; Hendra Harmi; Deri Wanto; Asri Karolina (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Education is very necessary, not to be separated from human life. The expansion and planting of education play an important role in shaping the personality of a student who has the quality and moral morality. Therefore, educators must make and think of the design in the future with an intimal that may be used to achieve the increasing learning activities of students by continuing to improve quality and professionalism in teaching an educator. So, it is expected that educators can play a maximum role in the learning process.This type of research is field research, namely research in which data collection is carried out in the field. In this case, this was done at Mes SAD, Muratara Regency. The method in research is used in research that produces qualitative descriptive data.In Mes Suku Anak Dalam (SAD), Muratara Regency, there are SAD children who are nurtured and guided by their caregivers and teachers to be directed and made like other modern children so that they can achieve their goals and be useful for the country and the nation. The Anak Dalam tribe is underestimated by others, other people think that SAD children are not the same as modern children, even though they are also ordinary humans, it's just that from their childhood they lived in remote places so they didn't keep up with the times, but now they It has changed a lot differently from the previous one, before they didn't want to wear clothes, didn't want to wear sandals, no cellphones, didn't go to school and so on, but now these SAD children in Mes have changed although little by little, now they are in the process of coaching by Mes SAD teachers and caregivers, they are guided and mentored by Mes SAD teachers and caregivers to study science and religious sciences.